Percutaneous Image-Guided Cryoablation of Metastatic Colorectal Adenocarcinoma to the Abdominal Wall - Jillian Drogin; Ahmed Abdelbaki; Justin Lendermon; Keith Pereira; Alejandro Mendez-Castillo (The Arab Journal of Interventional Radiology)
Abdominal wall metastases are rarely seen in primary colorectal cancer; the majority of cases are attributed to seeding from previous procedures. We report a case of percutaneous cryoablation of metastatic colorectal cancer to the abdominal wall with no evidence of recurrence 1 year later.